Changes in structure of over‐ and midstory tree species in a Mediterranean‐type forest after an extreme drought‐associated heatwave. (8th September 2019) - Steel, Emma J.; Fontaine, Joseph B.; Ruthrof, Katinka X.; Burgess, Treena I.; Hardy, Giles E. St. J.
Abstract: Worldwide, extreme climatic events such as drought and heatwaves are associated with forest mortality. However, the precise drivers of tree mortality at individual and stand levels vary considerably, with substantial gaps in knowledge across studies in biomes and continents. In 2010–2011, a drought‐associated heatwave occurred in south‐western Australia and drove sudden and rapid forest canopy collapse. Working in the Northern Jarrah ( Eucalyptus marginata ) Forest, we quantified the response of key overstory ( E. marginata, Corymbia calophylla ) and midstory ( Banksia grandis, Allocasuarina fraseriana ) tree species to the extreme climate event. Using transects spanning a gradient of drought impacts (minimal (50–100 m), transitional (100–150 m) and severe (30–60 m)), tree species mortality in relation to stand characteristics (stand basal area and stem density) and edaphic factors (soil depth) was determined. We show differential mortality between the two overstory species and the two midstory species corresponding to the drought‐associated heatwave. The dominant overstory species, E. marginata, had significantly higher mortality ( 19%) than C. calophylla ( 7%) in the severe zone. The midstory species, B. grandis, demonstrated substantially higher mortality ( 59%) than A. fraseriana ( 4%) in the transitional zone. Banksia grandis exhibited a substantial shift in structure in response to the drought‐associated heatwave in relation to tree size, basal area and soil depth. This study illustrates the role of climate extremes in driving ecosystem change and highlights the critical need to identify and quantify the resulting impact to help predict future forest die‐off events and to underpin forest management and conservation.